Lokalne prawo podatkowe - Sawicka, Krystyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
Local tax law constitutes the main instrument of implementing communal tax policy, even though the influence of commune bodies in this area is limited due to the scope of their law-making powers and a relatively simple structure of local taxes. Competences of communes in establishing the acts of local law concerning taxation do not result from their autonomy, but are implemented as an element of the decentralisation process of public finances as authorised by the state. Statutory provisions determine both limits of tax policy observed by communes and the instruments which they may apply. Additionally, if the instruments of policy in question are aimed at entrepreneurs, commune councils adopting relevant regulations are obliged to observe not only the provisions of the Polish tax law, but they are also to take into consideration the principles of granting state aid as determined by the EU and the national laws.
Keywords: prawo podatkowe; lokalne prawo podatkowe; nadzór regionalnych izb obrachunkowych; pomoc społeczna; akty prawa miejscowego